2017
DOI: 10.1371/journal.pone.0179533
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, trend and risk factors for antiretroviral therapy discontinuation among HIV-infected adults in Ethiopia in 2003-2015

Abstract: BackgroundIt is well acknowledged that antiretroviral therapy (ART) discontinuation hampers the progress towards achieving the UNAIDS treatment targets that aim to treat 90% of HIV diagnosed patients and achieve viral suppression for 90% of those on treatment. Nevertheless, the magnitude, trend and risk factors for ART discontinuation have not been explored extensively. We carried out a retrospective data analysis to assess prevalence, trend and risk factors for ART discontinuation among adults in Southwest Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 59 publications
6
33
0
Order By: Relevance
“…Most of the variables which found to have association with TF in this study were established facts to predict TF and are among the global recommendations to improve TF (8,(32)(33)(34). Among these, medication adherence, disclosure of HIV status, missed appointment to ART, history of ART exposure prior to initiation, residency and marital had significant association with VLS which is in line with most of the studies conducted in low and middle income countries (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 88%
“…Most of the variables which found to have association with TF in this study were established facts to predict TF and are among the global recommendations to improve TF (8,(32)(33)(34). Among these, medication adherence, disclosure of HIV status, missed appointment to ART, history of ART exposure prior to initiation, residency and marital had significant association with VLS which is in line with most of the studies conducted in low and middle income countries (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, from a health systems perspective, increasing risk tolerance among high-risk populations would not be optimal, especially if the patients are dependent on regular uninterrupted care (ART) to maintain good health. Various studies continue to show that adherence to ART is an ongoing challenge across the world [79][80][81]. As such, continued engagement with the healthcare system-which is facilitated by health insurance-is going to be critical for HIV care, as well as achieving the global HIV targets of 90-90-90 [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, many people find it very difficult to take ARVs drug as precisely as they should for a number of reasons. Some of the reasons for common and consistent barriers for ART adherence include: stigma, perceptions of side effects, lack of food, inadequate knowledge of ART, patient reported symptoms, stress, lack of social support, substance use, regimen complexity, self-efficacy for medication taking, depression (Edward., Machtinger & Bangsber., 2006;Tassie., 2010); gender, having immunological failure, having tuberculosis/HIV co-infection (Gesesew., Ward., Woldemichael., & Mwanri., 2017;Alagaw et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though level of adherence; associated factors and implications have become more and more recognized, studies about this issue still need further investigations particularly in Jimma zone government ART facilities-tremendously scale up to reach people with HIV particularly in rural and semi urban settings. Furthermore, though very few studies attempted to assess antiretroviral therapy discontinuations and identified some possible associated factors (Gesesew et al, 2017;Assefa., Taha., Dejene & Dube., 2013;Amberbir., Deribe., Hailekiros., Biadglign & Kebede., 2008;Tiyou et al, 2010). These studies were all of them based on sole, well organized study setting such as Jimma University Specialized Hospital ART clinic or Nekemte Hospital.…”
Section: Introductionmentioning
confidence: 99%